2022
DOI: 10.3390/ijms23063241
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Cross-Involvement in Acne Vulgaris and Hidradenitis Suppurativa: A Literature Review

Abstract: Acne Vulgaris (AV) and Hidradenitis suppurativa (HS) are common chronic inflammatory skin conditions that affect the follicular units that often coexist or are involved in differential diagnoses. Inflammation in both these diseases may result from shared pathways, which may partially explain their frequent coexistence. MicroRNAs (miRNAs) are a class of endogenous, short, non-protein coding, gene-silencing or promoting RNAs that may promote various inflammatory diseases. This narrative review investigates the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…miRs are involved in several steps of AV etiopathogenesis. miR-21 has pro-inflammatory effects and is also associated with the fibrotic process in patients with AV [12]. In the study by Ghumra et al [1], it was shown that miR-21 levels were increased in both the plasma and tissue of patients with AV and that this miR was an early marker for the development of atrophic scarring.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…miRs are involved in several steps of AV etiopathogenesis. miR-21 has pro-inflammatory effects and is also associated with the fibrotic process in patients with AV [12]. In the study by Ghumra et al [1], it was shown that miR-21 levels were increased in both the plasma and tissue of patients with AV and that this miR was an early marker for the development of atrophic scarring.…”
Section: Discussionmentioning
confidence: 96%
“…MicroRNAs (miRs) are small RNA molecules transcribed from RNA genes in protein-coding and non-proteincoding regions of the genome but are not translated into proteins [10,11]. miRs affect keratinocyte maturation and cooperation and participate in the pathogenesis of AV, resulting in different outcomes depending on the deficiency or overexpression of their levels [12].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned-above, various circulating miRNAs exhibit dysregulation in both HS-affected tissues and blood ( Wang et al, 2016 ). These miRNAs are recognized for their interactions with genes embedded within inflammatory pathways, encompassing Toll-like receptor signaling, cytokine production, and immune cell recruitment ( Borgia et al, 2022 ). As a consequence, it can be hypothesized that their dysregulation perpetuates HS-related inflammation and serves as indicative biomarkers for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple miRNA (miR-155, miR-223, miR-21, and miRNA-146a) levels were found to be altered in acne vulgaris. These miRNAs are related to pathogenetic aspects, such as the regulation of the innate immune response, regulation of the Th1/Th17 axis, and fibrosis processes that induce scar formation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%